Self-Perceived Problematic Use of Online Pornography Is Linked to Clinically Relevant Levels of Psychological Distress and Psychopathological Symptoms. - Mennig, Manuel; Tennie, Sophia; Barke, Antonia (Archives of Sexual Behavior, 2022)
Online pornography is a widespread Internet application. As with other Internet applications, in some cases its use can become problematic. First indications point to a link between problematic use of online pornography and psychological distress and general functional impairment. However, to date, there are no standardized criteria for assessing problematic use of online pornography. In this study, we used the Online Pornography Disorder Questionnaire (OPDQ)—an instrument which adapted the official criteria for Internet Gaming Disorder to online pornography—to measure problematic use and investigated to what extent consumers with a self-perceived problematic use of online pornography differed from casual users with regard to their psychological distress. An online sample of German adult visitors to a popular casual dating site completed the OPDQ, the Brief Symptom Inventory (BSI), and provided information on their online pornography use (n = 1539; 72.6% male; 31.43 ± 11.96 years). T-scores for the BSI were calculated and independent t-tests were conducted to compare casual users with consumers with a self-perceived problematic use of online pornography. Of the users, 5.9% fulfilled the criteria for problematic use. This group consumed online pornography for longer amounts of time and showed higher levels of psychological distress (Hedges' g from 0.75 to 1.21). The T-scores of users with self-perceived problematic online pornography use reached clinically relevant levels on all subscales. Overall, the results of the study indicate that self-perceived problematic use of online pornography seems to be linked to severe psychological distress that may warrant clinical attention.